Rod and S-cone driven ERG signals at high retinal illuminances - Kremers, Jan; Czop, Dariusz; Link, Barbara (Documenta Ophthalmologica, 2009)
The purpose of the present study was to investigate whether L- and M-cone driven responses can be influenced by concomitant modulation in the rods or the S-cones. In addition, it was studied whether a change in the state of adaptation in L- or M-cones can have a different influence on ERG data when simultaneously the mean number of photoisomerizations in either rods or S-cones is altered. It was found that rods and/or S-cones cannot be neglected when measuring L- or M-cone driven ERGs.
Keywords: Electroretinogram; Rod driven signals; S-cone driven signals; Temporal frequency; Retinal illuminance